Cross-cultural adaptation and validation of the self-reporting questionnaire among HIV+ individuals in a rural ART program in southern Uganda - Nakimuli-Mpungu, E. (Informa UK Limited, 2012)
Background HIV treatment programs are in need of brief, valid instruments to identify common mental disorders such as depression. Aim To translate and culturally adapt the Self-Reporting Questionnaire (SRQ-20) for use in Uganda and to investigate its psychometric properties in this setting. Methods Following an initial translation of the SRQ-20 from English to Luganda, key informant interviews and focus-group discussions were used to produce a culturally adapted version of the instrument. The adapted SRQ-20 was administered to 200 HIV-positive individuals in a rural antiretroviral therapy program in southern Uganda. All study participants were also evaluated by a psychiatric clinical officer with the Mini International Neuropsychiatric Interview (MINI). Receiver-operating-characteristic analysis was used to examine the sensitivity and specificity of the SRQ-20 compared to the clinical diagnosis generated by the MINI. Results The prevalence estimates of any depressive disorder and current depression were 24% (n = 48) and 12% (n = 24), respectively. The SRQ-20 scores discriminated well between subjects with and without current depression based on the MINI, with an area under the curve of 0.92, as well as between subjects with and without any current or past depressive disorder, with an area under the curve of 0.75. A score of 6 or more had 84% sensitivity and 93% specificity for current depression, and 75% sensitivity and 90% specificity for any depressive disorder. Conclusion The SRQ-20 appears to be a reliable and valid screening measure for depression among rural HIV-positive individuals in southern Uganda. The use of this screening instrument can potentially improve detection and management of depression in this setting.